Comparison of the game structure and point ending during Grand Slam women's doubles tennis - Borderias, M.; Crespo, M.; Martínez-Gallego, R.; Baiget, E. (International Journal of Sports Science & Coaching, 2023)
Despite the importance of doubles tennis, there is little research on this modality of the game, especially as per women play. The aim of this study was to analyse the structural variables and the way points ended in women's doubles, as well as to observe the differences between surfaces and between winning and losing teams. Twenty-one WTA doubles matches from three Grand Slams played on three different surfaces were analysed. Players played 2.0 ± 0.3 sets, 19.9 ± 3.2 games, 130.4 ± 25.3 points, 0.2 ± 0.6 tie breaks per match (PM), 9.5 ± 1.0 games and 62.6 ± 7.9 points per set, and 6.6 ± 0.6 points per game (PG). 33.5% of the points ended with a winner (Wn), 43.6% with a forced error (FE) and 22.8% with an unforced error (UE), with the Wn shot being the variable that most discriminated between winner and loser teams. It was also shown that the way more points were finished was with FE, followed by Wn and UE. There were no significant differences between surfaces in structural variables or point ending. These results showed that in women's doubles playing Wn shots and avoiding UE is crucial to successful performance, so that aggressive play and taking the initiative in the game has a positive influence in the result.